PAUD BERKUALITAS MELALUI PERAN PENDIDIK SEBAGAI PEMIMPIN DALAM KOMUNITAS DAN ORGANISASI HIMPAUDI KABUPATEN TANGERANG - Mutoharoh, Mutoharoh; Rusmalina, Euis; Asfar, Andi Hasryningsih; Maliki, Budi Ilham; Subroto, Desty Endrawati; Sariwardani, Andriani; Umalihayati, Umalihayati; Sofiah, Siti; Elinawati, Elinawati; Suhdiyah, Dede (LPPM IAI Dar Aswaja Rokan Hilir, 2025)
Early Childhood Education (PAUD) plays an important role in forming the foundation of holistic child development. This article discusses how the role of educators as leaders in the PAUD community and the HIMPAUDI organization can be key to improving the quality of PAUD services. Through effective leadership, educators not only carry out learning functions, but also drive innovation, strengthen collaboration between educators, and build productive partnerships with parents and the community. HIMPAUDI as a professional organization plays a strategic role in supporting the development of educator leadership capacity through training, coaching, and advocacy. This article describes the importance of strengthening the role of educator leadership and developing organizational networks in realizing quality, inclusive, and sustainable PAUD, especially in the Tangerang Regency area. The findings show that trained educator leadership and strong organizations contribute significantly to improving the quality of PAUD and optimal early childhood development.